Quality of Life and Self-Care Behaviour during Dysmenorrhea among Adolescents of Pokhara - lamsal, Anuska; Pokhrel, Subash (Tribhuvan University Journal, 2026)
After menarche, many adolescent girls experience menstrual problems such as irregular menstruation, excessive bleeding, and dysmenorrhea. Among these, dysmenorrhea is highly prevalent and can interfere with daily activities, affecting both physical and emotional well-being and negatively impacting quality of life. Many adolescents rely on home remedies and self-care measures to relieve menstrual pain, often without seeking professional medical care. This study aimed to assess the quality of life and self-care behavior during dysmenorrhea among adolescents in Pokhara. A quantitative descriptive cross-sectional design was employed, involving 206 adolescent students selected through total enumeration sampling. Data were collected using a self-administered questionnaire covering socio-demographic characteristics, anthropometric measurements, menstrual history, quality of life, and self-care behaviors. Analysis was performed using the Statistical Package for Social Sciences (SPSS) version 16.0. The mean age of participants was 14.66 years, and the prevalence of dysmenorrhea was 74.3%. More than half of the participants (62.1%) reported a reduced quality of life, while 48.4% demonstrated poor self-care behaviors during menstrual pain. Common self-care practices included ignoring the pain (91.5%), using a hot water bag (73.2%), and taking over-the-counter medications (15.7%). Dysmenorrhea was significantly associated with age at menarche, menstrual bleeding volume, passage of clots, and family history. Despite its prevalence and impact, many adolescents neglected pain management and did not seek medical attention. These findings highlight the need for educational interventions to orient girls entering menarche about effective self-care strategies and menstrual health management. Incorporating menstrual education into school curricula could improve quality of life and promote better health practices.